Effects of English Teachers’ Classroom Feedback on Students - Kshetree, Arun Kumar; Bhusal, Tilak; K. C, Kamala; Jyoti, Rameshor; Pokhrel, Prem Raj (Butwal Campus Journal, 2024)
The feedback in the English and other classrooms may not be the same as there is more to do in English language teaching(ELT) classes. The students need to practice speaking English, and they need to learn to use English in their day-to-day lives. The teachers use different feedback in different situations in the class, which may have different impacts on the behavior of the students. The effect of the feedback differs according to the familiarity of the teacher among the students, classroom culture and environment, the students’ levels as well as the type of feedback. This study is based on the narrative inquiry method, and the qualitative data were collected from seven well-experienced English teachers teaching in the secondary schools in Rupandehi. The teachers suggested different ways of managing feedback in the English classes and strategies for solving problems due to negative feedback in the classes. The results may be useful to all the teachers to be skillful in making positive feedback and managing a good classroom environment even if the negative impact of feedback is seen in the class to make the teaching-learning environment better.